Curcumin phytosomal softgel formulation: Development, optimization and physicochemical characterization - Allam Ahmed N.; Komeil Ibrahim A.; Abdallah Ossama Y. (Acta Pharmaceutica)
Curcumin, a naturally occurring lipophilic molecule can exert multiple and diverse bioactivities. However, its limited aqueous solubility and extensive presystemic metabolism restrict its bioavailability. Curcumin phytosomes were prepared by a simple solvent evaporation method where free flowing powder was obtained in addition to a newly developed semisolid formulation to increase curcumin content in softgels. Phytosomal powder was characterized in terms of drug content and zeta potential. Thirteen different softgel formulations were developed using oils such as Miglyol 812, castor oil and oleic acid, a hydrophilic vehicle such as PEG 400 and bioactive surfactants such as Cremophor EL and KLS P 124. Selected formulations were characterized in terms of curcumin in vitro dissolution. TEM analysis revealed good stability and a spherical, self-closed structure of curcumin phytosomes in complex formulations. Stability studies of chosen formulations prepared using the hydrophilic vehicle revealed a stable curcumin dissolution pattern. In contrast, a dramatic decrease in curcumin dissolution was observed in case of phytosomes formulated in oily vehicles.